132P Correlation between tumour infiltration lymphocyte and PDL-1 expression in laryngeal cancer and its prognostic significance: A prospective, non-interventional trial. (15th December 2019) - Ismail, M; Wakiel, H El; Ghany, D Abd El; Shakweer, M M; Lotfy, A; Gaballah, A M
Abstract: Background: Immune system plays an important role in cancer evolution. However, cancer cells affect the immune system and use it for its growth and survival. Tumour infiltration lymphocytes and PDL-1 expression proved to play an important prognostic role in different malignancies. We aimed at evaluating this role in laryngeal cancer. Methods: We prospectively analyzed the pre-treatment paraffin blocks for laryngeal cancer patients, whether on the laryngoscopy or operative specimens, to identify the CD8-positive cells in the tumour epithelium or stroma and the PDL-1 expression on the tumour cells. Appropriate tissue was used as positive control; placenta for PDL-1 and tonsil for CD8. A total score formed of the sum of percentage and intensity of PDL-1. A final comprehensive rate was considered as low expression when combined percentage and intensity score from 0 to 4, and high expression when score from 5-7. According to the distribution, the CD8+T cell invasion was divided into strong infiltration (> 10/100 of epithelial cells; >20/100 stromal cell infiltration) and weak infiltration (< 10/100 epithelial cells; < 20/100 stromal cell infiltration). Results: 40 patients were included in our study; 12 patients had early stage disease (I or II) and 28 with advanced stage (III or IV). PDL-1 expression was positive in 92.5%. Neither the PDL-1 nor CD-8 were found significantly correlated to OS in the whole population, however patients with advanced stage, median OS was significantly low for negative or low compared to high PDL-1 expression (11.7 vs 25.2 months (p = 0.036)), a trend of better OS in high CD8 Epithelial expression (25.1 versus 15.9, P = 0.514) and again trend of higher OS in high CD8 Stromal expression (25.3 versus 15.6 months, p = 0.375). Also there were significant correlation between the CD8 expression in the tumour epithelium and stroma with the PDL-1 expression with p-value of 0.001 and < 0.0001 respectively. Conclusion: There is a positive correlation between tumour infiltration lymphocytes and PDL-1 expression in laryngeal squamous carcinoma and the higher PDL-1 expression in advanced stage laryngeal cancer is associated with better OS. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.